(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Bibliotherapy is the use of literature to facilitate the psychotherapeutic process and therapeutic reading is often used as an adjunct to various psychotherapy modalities. This paper presents a talk reporting on the initial findings of the use of bibliotherapy in existential psychotherapy, as three existential-phenomenological therapists have experienced it.